Particulate Matter 10 (PM(10)) Is Associated with Epistaxis in Children and Adults - Kim, Kyungsoo (Int J Environ Res Public Health, 2021)
The impact of atmospheric concentration of particulate matter ≤10 μm in diameter (PM(10)) continues to attract research attention. This study aimed to evaluate the effects of meteorological factors, including PM(10) concentration, on epistaxis presentation in children and adults. We reviewed the data from 1557 days and 2273 cases of epistaxis between January 2015 and December 2019. Eligible patients were stratified by age into the children (age ≤17 years) and adult groups. The main outcome was the incidence and cumulative number of epistaxis presentations in hospital per day and month. Meteorological factors and PM(10) concentration data were obtained from the Korea Meteorological Administration. Several meteorological factors were associated with epistaxis presentation in hospital; however, these associations differed between children and adults. Only PM(10) concentration was consistently associated with daily epistaxis presentation in hospital among both children and adults. Additionally, PM(10) concentration was associated with the daily cumulative number of epistaxis presentations in hospital in children and adults. Furthermore, the monthly mean PM(10) concentration was significantly associated with the total number of epistaxis presentations in the corresponding month. PM(10) concentration should be regarded as an important environmental factor that may affect epistaxis in both children and adults.